2015
DOI: 10.1016/j.cmi.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of nosocomial infections due to ESBL-positive Enterobacteriaceae in Germany: data from the German National Reference Center for the Surveillance of Nosocomial Infections (KISS)

Abstract: Surveillance systems for hospital infections are reporting increasing rates of extended-spectrum β-lactamase (ESBL)-positive Enterobacteriaceae in Europe. We aimed to perform a national survey on this trend and on the regional distribution of nosocomial infections due to ESBL-positive Enterobacteriaceae in German hospitals. Data from 2007 to 2012 from two components of the German national nosocomial infection surveillance system were used for this analysis. The data derive from intensive care units and surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
8
21
1
8
Order By: Relevance
“…Antimicrobial‐resistant bacterial infection and colonization, especially after surgery, is a major global clinical problem that is expected to continue to increase in parallel with the increase in the elderly population. The AMR bacterial infection rates in the present survey were lower than those previously reported . VRE or MDR‐GN was not isolated from any of the patients who participated in the present survey.…”
Section: Discussioncontrasting
confidence: 80%
“…Antimicrobial‐resistant bacterial infection and colonization, especially after surgery, is a major global clinical problem that is expected to continue to increase in parallel with the increase in the elderly population. The AMR bacterial infection rates in the present survey were lower than those previously reported . VRE or MDR‐GN was not isolated from any of the patients who participated in the present survey.…”
Section: Discussioncontrasting
confidence: 80%
“…pneumoniae, E. coli, others8444NDTanzania [56]2012UniversityBothChildren, adultsPusDDSTK. pneumoniae, E. coli, others2979NDTanzania [36]2007UniversityBothChildren, adultsUrine, pus, blood d PCR-SequencingK. pneumoniae, E. coli, P. aeruginosa, others22735VIM (12.3 %), OXA-48 (4.9 %), KPC (3.5 %), NDM (3.1 %)Tanzania [57]2012UniversityBothChildren, adultsWoundDDSTPseudomonas spp, Proteus spp, K. pneumoniae, E. coli11735NDTanzania [58]2011UniversityBothChildren, adultsWoundDDSTK.…”
Section: Resultsmentioning
confidence: 99%
“…However the East African proportion is considerably higher than averages reported for resource-rich countries. For instance, the average ESBL proportion estimates reported in a nationwide hospital survey in Germany for 2012 were in the 10 to 15 % range [36]. In 2012, a study for nine US census regions reported ESBL proportion estimates in the 4 to 12 % range [37], while a 9-year survey in Japan recorded a proportion estimate of 6.3 % in 2003 increasing to 10–20 % in 2011 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors, we found that ESBL-E carriage was associated with frequent consumption of pork. In addition, data from KISS showed high incidences of nosocomial infections with ESBL-E in North Rhine-Westphalia and Thuringia [3]. Interestingly, these German federal states are associated with high consumption of meat, mainly pork (German National Nutrition Study II, 2008).…”
Section: The Association Of Esbl-producing Enterobacteriaceae (Esbl-ementioning
confidence: 99%